Mapping factors that boost employee productivity - Rafli Adri Refianto; Meita Pragiwani (Jurnal Riset Manajemen dan Bisnis, 2025)
This study aims to identify and map the key factors that enhance employee productivity at PT NEIA Services in Tangerang City, focusing on three critical determinants: teamwork, work motivation, and compensation. This research employs a quantitative approach with an associative strategy. Data were collected through saturated sampling of all 80 employees using structured questionnaires based on a Likert scale distributed via Google Form. The data analysis employed multiple linear regression, partial coefficient of determination, and t-test hypothesis testing using SPSS version 25. The findings provide a clear map of productivity drivers, demonstrating that all three factors significantly enhance employee productivity. Both teamwork and compensation show statistically significant positive effects, while work motivation exhibits a substantial positive influence on productivity outcomes. This research offers valuable insights for organizational management by highlighting strategic areas for intervention. The results suggest that optimized teamwork structures, enhanced motivation systems, and competitive compensation schemes serve as powerful levers for boosting workforce performance and organizational effectiveness.